Altered CYP19A1 and CYP3A4 Activities Due to Mutations A115V, T142A, Q153R and P284L in the Human P450 Oxidoreductase - Udhane, Sameer S.; Parween, Shaheena; Kagawa, Norio; Pandey, Amit V. (Frontiers in Pharmacology, 2017)
All cytochromes P450s in the endoplasmic reticulum rely on P450 oxidoreductase (POR) for their catalytic activities. Mutations in POR cause metabolic disorders of steroid hormone biosynthesis and affect certain drug metabolizing P450 activities. We studied mutations A115V, T142A, Q153R identified in the flavin mononucleotide (FMN) binding domain of POR that interacts with partner proteins and P284L located in the hinge region that is required for flexibility and domain movements in POR. Human wild type and mutant POR as well as CYP3A4 and CYP19A1 proteins in recombinant form were expressed in bacteria, and purified proteins were reconstituted in liposomes for enzyme kinetic assays. Quality of POR protein was checked by cytochrome c reduction assay as well as flavin content measurements. We found that proteins carrying mutations A115V, T142A located close to the FMN binding site had reduced flavin content compared to wild type POR and lost almost all activity to metabolize androstenedione via CYP19A1 and showed reduced CYP3A4 activity. The variant P284L identified from apparently normal subjects also had severe loss of both CYP19A1 and CYP3A4 activities, indicating this to be a potentially disease causing mutation. The mutation Q153R initially identified in a patient with disordered steroidogenesis showed remarkably increased activities of both CYP19A1 and CYP3A4 without any significant change in flavin content, indicating improved protein-protein interactions between POR Q153R and some P450 proteins. These results indicate that effects of mutations on activities of individual cytochromes P450 can be variable and a detailed analysis of each variant with different partner proteins is necessary to accurately determine the genotype-phenotype correlations of POR variants.